PENGARUHKUALITAS AUDITOR, JUMLAH KOMITE AUDIT DAN PENDIDIKAN KETUA KOMITE AUDIT TERHADAP ERANINGS MANAGEMENT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTARDI BURSA EFEK INDONESIA TAHUN 2010-2012 - Ni Made Sunarsih (Universitas Pendidikan Nasional, 2017)
Earnings managements are actions by companies to manipulate financial statements. The financial statements should be able to provide reliable information and presents the actual performance so as not to be mislead the user. This study aims to examine the effect of auditor quality, number of audit commitee and education of audit committee chairman to earnings managemnets. The research was conducted at manufacturing companies listed on BEI, method of determining the samples using purposive sampling method with total sample of 137. Data analysis using multiple linier regression analysis. The result of the research shows that auditor quality and education of audit committee chairman have no effect on earnings managemnets, while number of audit committee have negatife effect to earning managemnets.Keywords: Eranings management, auditor quality, number of audit commitee and education of audit committee chairman